Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
P=a²√3/4
P=√3 j²
√3=a²√3/4/*4
4√3=a²√3/:√3
a²=4
a=√4=2
P=4√3 j²
4√3=a²√3/4 /*4
16√3=a²√3/:√3
a²=16
a=√16=4
Odpowiedź:
[tex]p = \frac{ {a}^{2} \sqrt{3} }{4} \\[/tex]
a)
[tex] \frac{ {a}^{2} \sqrt{3} }{4} = \frac{ \sqrt{3} }{2} \\ {a}^{2} = \frac{ \sqrt{3} }{2} \times \frac{4}{ \sqrt{3} } = 2 \\ a = \sqrt{2} [/tex]
b)
[tex] \frac{ {a}^{2} \sqrt{3} }{4} = \frac{4 \sqrt{3} }{2} \\ {a}^{2} = \frac{4 \sqrt{3} }{2} \times \frac{4}{ \sqrt{3} } = 8 \\ a = \sqrt{8} = 2 \sqrt{2} [/tex]